Phenol removal onto novel activated carbons made from lignocellulosic precursors: Influence of surface properties - Valente Nabais, Joao (2009)
The adsorption of phenol from dilute aqueous solutions onto new activated carbons (AC) was studied. The novel activated carbon was produced from lignocellulosic (LC) precursors of rapeseed and kenaf. Samples oxidised with nitric acid in liquid phasewere also studied. The results have shown the significant potential of rapeseed and kenaf for the activated carbon production. The activated carbons produced by carbon dioxide activation were mainly microporous with BET apparent surface area up to 1350m2 g−1 and pore volume 0.5cm3 g−1. The effects of concentration (0.1–2mM) and pH (3–13) were studied. The phenol adsorption isotherms at 25 ◦C followed the Freundlichmodel withmaximumadsorption capacities of approximately 80 and 50mgg−1 for the pristine and oxidised activated carbons, respectively. The influence of pH on the adsorption has two trends for pH below and above 10. It was possible to conclude that when phenol is predominantly in the molecular form the most probable mechanism is based on the – dispersion interaction between the phenol aromatic ring and the delocalised electrons present in the activated carbon aromatic structure. When phenolate is the major component the electrostatic repulsion that occurs at high pH values is the most important aspect of the adsorption mechanism.